Literature Review: Faktor-Faktor Dalam Pemasaran Dan Pengembangan UMKM - Aditiya, Variza; Mustafa, Said; Lastri, Novelma; Hartutik, Dwi; Desy Musdiana, Andi (LPPM STISIP IMAM BONJOL, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in a country's economy, particularly in creating employment opportunities, increasing community income, and driving economic growth. However, the development of MSMEs often faces various challenges, such as limited access to capital, technology, markets, and managerial capabilities. This literature review aims to analyze various studies related to the development of MSMEs, focusing on factors that influence their growth and sustainability, as well as strategies that can be implemented to address these challenges. Some key findings indicate that improving access to financing, entrepreneurship training, adoption of digital technology, and government policy support are critical elements in promoting MSME development. Additionally, collaboration between MSME actors, financial institutions, and the government is deemed effective in creating an ecosystem that supports MSME growth. This literature review is expected to provide insights for stakeholders in designing more effective and sustainable MSME development strategies.